Health education on the use of aromatherapy as an effort to control hypertension - salsa - wijayanti; Erni setiyorini; Sandi Alfa Wiga Arsa; Anita Rahmawati (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Hypertension is a non-communicable disease with increasing prevalence and is a major risk factor for cardiovascular disease, especially in the elderly. Low knowledge, unhealthy lifestyles, and suboptimal stress management often lead to uncontrolled hypertension in the community. Housewives have the potential to be empowered as a socio-religious community in efforts to control hypertension. This community service activity aims to increase the knowledge and independence of subjects in controlling hypertension through health education and the application of complementary lavender aromatherapy therapy. The activity method uses a pretest–posttest design approach without a control group, with housewives as subjects who are members of the Surah Yasin reading group. The sample was taken by accidental sampling, with a total of 50 people. Respondents were given education about hypertension and trained to use lavender aromatherapy provided by the researcher, then their blood pressure was evaluated. The instruments used were questionnaires and sphygmomanometer aneroid. The results of the activity were analyzed descriptively, showing an increase in knowledge in the good category from 26% before the activity to 78% after the activity and a decrease in average systolic blood pressure of 9.36 mmHg and diastolic blood pressure of 5.68 mmHg. This activity shows that a community-based approach through health education and lavender aromatherapy has the potential to support promotive and preventive efforts in controlling hypertension in the community.Keywords: hypertension